The Effect of Financial Resources on Homeownership, Marriage, and Fertility - Bulman, George,Goodman, Sarena,Isen, Adam (National Bureau of Economic Research, 2022)
This paper leverages the universe of U.S. tax data and state lottery wins between 2000 and 2019 to estimate the causal effect of financial resources on three key lifecycle outcomes for young adults. We find large and persistent effects on homeownership, with a response function that exhibits substantial concavity but also an extremely high upper bound, and larger responses among higher-income individuals. Resources generate persistent increases in marriage for single men and women but do not increase the likelihood existing marriages are preserved. Fertility is modestly accelerated by a lottery win, but there is little effect on total fertility. Our results support a causal pathway behind differences in homeownership and marriage by socioeconomic status and inform theories of household formation and the family
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Glücksspiel; Vermögen; Wohneigentum; Ehe; Fertilität; USA; Household Behavior and Family Economics; Household Finance; Marriage; Marital Dissolution; Family Structure; Domestic Abuse; Fertility; Family Planning; Child Care; Children; Youth; Housing Demand